Geochronology and petrogenesis of Eocene gabbros and granitic rocks of the eastern Gangdese belt, southern Tibet: Implications for the timing of India-Asia collision - Shui, Xin Fang; Klemd, Reiner; He, Zhen Yu; Mao, Jing Wen; Zhao, Yuan Yi (Gondwana Research, 2021)
The Palaeocene-Eocene (66–41 Ma) hosts the most intense stage of extensive magmatism in the Gangdese belt of southern Tibet. However, the magma sources and tectonic setting of this magmatic belt have been a matter of discussion for decades. In this study, we conducted zircon geochronological and geochemical studies on Eocene gabbroic rocks and granitic rocks from the Jiacha area in the eastern Gangdese belt. Laser ablation-ICP-MS zircon U–Pb dating suggests almost synchronous crystallization ages of 50–47 Ma for both rock types. Geochemically, the gabbroic rocks have low total rare earth elements and high positive zircon εHf(t) values (from +8.4 to +15.0), indicating that the parental magma was derived from an isotopically depleted mantle. The granitic rocks are magnesian calc-alkalic to calcic granites that are characterized by variable zircon εHf(t) values (from +3.0 to +10.8), indicating that the magmas were generated by differentiation of a mantle-derived magma with variable contributions from ancient crustal materials. Furthermore, an enlarged database of 66–41 Ma plutonic rocks and coexisting Linzizong volcanic rocks reveals an evolutionary trend from mafic to silicic rocks. The zircon Hf and Nd isotopic compositions become more evolved with increasing whole-rock SiO2. The whole-rock and isotope geochemistry of the 66–41 Ma plutonic rocks and the Linzizong volcanic rocks indicate an origin and evolution of these rocks in an active continental margin setting. Therefore, we argue that the Gangdese belt was associated with the subduction of the Neo-Tethyan Oceanic plate throughout the Early Eocene, thereby implying that the initial India-Asia collision occurred after 41 Ma.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Gangdese belt; Neo-Tethyan Oceanic subduction; Palaeocene-Eocene; Volcanism–Plutonism link